EVALUATION OF ANNATTO (Bixa orellana L) GENOTYPES THROUGH THE MORPHOLOGICAL CHARACTERISTICS OF FRUITS, SEEDS PRODUCTIVITY AND BIXIN CONTENT - Nilton César Mantovani; Magali Ferrari Grando; Aloisio Xavier; Wagner Campos Otoni (Ciência Florestal, 2013)
http://dx.doi.org/10.5902/198050989281 Bixa orellana L. (annatto) is considered an important source of natural colorants for food, pharmaceutical and textile industries and Brazil is one of the largest producers and exporters of this natural dye extracted from this plant. The morphological characterization of fruits, evaluation of  seed productivity and the content of carotenoid bixin present in freshly harvested and stored seeds for periods of 30, 60, 90 and 120 days, were performed on 10 genotypes of annatto to provide subsidies for the selection of superior genotypes for these characteristics. There were variations in all evaluated characteristics between the 10 genotypes. The fruit of all genotypes are covered with bristles or hairs, have reddish, green, yellow or red color, and two basic forms, oval or lanceolate. The fruits had average lengths ranging from 3.1 to 4.8 cm, and widths between 2.4 to 3.1 cm. The average number of seeds per fruit ranged from 41.5 to 50.6. The mass of 100 seeds varied from 1.1 to 2.24 g. There was significant difference in the concentration of bixin among genotypes, being possible to identify genotypes with high levels of bixin carotenoid (5.05%), superior to those already reported by other studies. The content of bixin decreased with the increase in the period of storage of seeds.